Analysis of Benzene-Induced Effects on Rhodococcus sp. 33 Reveals that Constitutive Processes Play a Major Role in Conferring Tolerance - Tony Gutiérrez; Robert Learmonth; Iain Couperwhite (The Scientific World Journal)
Most studies investigating mechanisms that confer microorganisms with tolerance to solvents have often focused on adaptive responses following exposure, while less attention has been given to inherent, or constitutive, processes that prevail at the onset of exposure to a toxic solvent. In this study, we investigated several properties of the highly solvent-tolerant bacterium Rhodococcus sp. 33 that confer it with a tolerance to high concentrations of benzene. When challenged with liquid benzene, the growth of both nonadapted and adapted cells was decreased by 0.25¨C0.30% (v/v) liquid benzene, and higher concentrations (≤0.35% v/v) produced a complete cessation in the growth of only nonadapted cells. When exposed to presolubilized benzene, nonadapted cells tolerated ≥1000 mg/l, whereas adapted cells tolerated >1400 mg/l. Measuring the cell membrane fluidity of the cells during these exposure experiments showed that at the onset of exposure, the membranes of adapted cells were less affected by benzene compared to nonadapted cells, although these effects were insignificant in the long term. Several benzene-sensitive mutants were generated from this Rhodococcus, two of which were unable to degrade benzene, yet they still tolerated 500¨C800 mg/l. This confirmed our earlier work suggesting that the benzene-degradation pathway of this organism plays a minor role in tolerance. Under the phase and transmission electron microscope, the mutants were found to have lost the ability to produce extracellular polymers, and many cells appeared pleomorphic, containing intracellular membrane invaginations and mesosome-like structures. As will be discussed, these results identify important functions of the cell membrane, the cell wall, and extracellular polymer in their native state (i.e., before exposure) in conferring this organism with tolerance to benzene.